A Study on the Production of Hydrocarbons from Used Thermoplastics in the Republic of Congo - Berry, Ulrich; Mabelet, Lagloire Bienvenu (Darul Yasin Al Sys, 2025)
End-of-life plastics represent a major hazardous waste stream worldwide, with an estimated 353 million tons of plastic waste generated in 2019 (Global Plastics Outlook, 2019). Their non-biodegradable nature causes significant environmental and health problems, including landscape degradation, proliferation of harmful insects, and fire hazards, with toxic smoke posing serious risks to human health. In the context of high demand for raw materials and the depletion of petroleum resources, the management of these wastes has become a critical environmental challenge, making recycling and energy recovery from plastics an essential component of sustainable development strategies. The aim of this study is to convert these wastes into fuels, thereby providing both economic and ecological benefits. Among the possible processes, pyrolysis is preferred because it decomposes plastics at lower temperatures than incineration or gasification, reducing the risk of metal evaporation and the release of other toxic substances. Therefore, pyrolysis emerges as an effective solution to reduce the volume of used plastics while producing reusable hydrocarbons.